Função do direito como síntese promocional e reforço de vínculo de progressividade - Zerneri, Márcio Barbosa (2017)
In the present work, starting from a sociological view on legal systems, was possible to verify that social organization adapt to the new order imposed by the Democratic State of Right, to surpass formal dimension, was necessary creates a functional restructuring using affirmative actions, offering positive or negative benefits. This technique is a set of laws, policies, guidelines, and administrative practices, to discourage undesirable behaviors and encourage desired behaviors, using rewards and social benefits. The proposal of the social doctrine was considered to overcome the liberal-individual model. For the individual to be able to achieve full development in society, a relationship of interdependence is necessary, thus requiring mutual and reciprocal commitments that allow the progress of both. The State is subject to the Law, and is therefore a provider of services to the population. Good public management is the fruit of obedience to the laws and the ruler uses state power for the common good. The Constitution of 1988 adopted a model of participatory democracy, in which both the people and the state are subject to national legislation. The promotional function of law, whose legal duty is tied to the constitutional nucleus, enables the realization of fundamental and social rights, compelling the actions of the state powers in this directive. In accepting this perspective of links and guidelines as the basis of the legal duty that compels the State to legislate and enforce fundamental social rights, it must be admitted that these material manifestations are the result of a synthesis. In this way, the thesis is presented that the effectiveness based on the previous reasoning occurs through a promotional synthesis, since the bonds and guidelines condition the future actions of the State (executive / legislative / judiciary) to achieve determined purposes. These results are effected as structural renovations (laws, programs, benefits and individual and collective decisions) that, when born of effectiveness, reinforce referentially the constitutional progressivity